2004
DOI: 10.1002/hup.600
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and polysomnographic effects of milnacipran on sleep in depressed patients

Abstract: The effects of milnacipran (50 mg bid) on sleep patterns of eight depressed inpatients, treated for 4 weeks, were studied during the initial (days 1-3) and terminal (days 26-28) treatment periods and compared with those obtained from three sleep recordings performed just prior to the initiation of the treatment. The clinical evolution of patients was evaluated weekly using the MADRS depression scale and the Spiegel and Norris sleep scales. Clinical improvement, shown by a mean reduction of 58% in MADRS scale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…Interestingly, in another study, milnacipran administration in depressed subjects improved sleep only when depression was also improved, further supporting the finding that milnacipran does not affect sleep continuity directly. 30 The lack of agreement between sleep diaries and PSG is consistent with reports from the literature that good sleepers show concordance between PSG and sleep diaries while poor sleepers do not.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, in another study, milnacipran administration in depressed subjects improved sleep only when depression was also improved, further supporting the finding that milnacipran does not affect sleep continuity directly. 30 The lack of agreement between sleep diaries and PSG is consistent with reports from the literature that good sleepers show concordance between PSG and sleep diaries while poor sleepers do not.…”
Section: Discussionsupporting
confidence: 89%
“…Treatment with another SNRI, milnacipran, did not show significant changes on sleep PSG parameters. No effect was observed on REM sleep, and only one study found increased ROL [ 86 ]. The study of Rahmani et al [ 87 ] reported increased total awake time and decreased NREM sleep after 7 days of milnacipran treatment of depressive patients.…”
Section: The Effects Of Antidepressants On Sleepmentioning
confidence: 99%
“…Duloxetine demonstrates effectiveness in reducing PTSD nightmares ( 70 ) and has a similar effect on sleep as venlafaxine ( 71 ): reduced length of REM sleep, fragmented sleep, and increase in periodic limb movement. For milnacipran , no increase in dream recall was observed ( 72 ).…”
Section: Effects Of Antidepressants On Dream Recallmentioning
confidence: 99%